2002
DOI: 10.1111/j.1748-0361.2002.tb00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need Among Rural Medicaid Beneficiaries in Minnesota

Abstract: Given the vulnerabilities of rural residents and the health care issues faced by the Medicaid population generally, the combined effects of being on Medicaid and living in a rural area raise important questions about access to health care services. This study looks at a key dimension of health care access: unmet needfor health care services. The study relies on data from a 1998 survey of rural Minnesota Medicaid beneficiaries. An overall response rate of 70% was obtained. For this study, the sample is limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…While expansion of Medicaid eligibility and elimination of healthcare coverage barriers may facilitate health insurance coverage, we should be cautious in anticipating better health outcomes for all cancer survivors, particularly since previous studies report rural-urban disparities among Medicare beneficiaries (13, 42). …”
Section: Discussionmentioning
confidence: 99%
“…While expansion of Medicaid eligibility and elimination of healthcare coverage barriers may facilitate health insurance coverage, we should be cautious in anticipating better health outcomes for all cancer survivors, particularly since previous studies report rural-urban disparities among Medicare beneficiaries (13, 42). …”
Section: Discussionmentioning
confidence: 99%
“…As suggested by the interviewees, disabled rural residents with Medicaid may face special challenges. A survey of rural Minnesota residents on Medicaid found that persons reporting that health problems or impairments limit their daily activities experienced higher rates of unmet health needs than other Medicaid recipients, even after controlling for demographic characteristics (Long, Coughlin, and Kendall 2002). One‐third of respondents reporting unmet needs blamed problems with the availability of providers.…”
Section: Discussionmentioning
confidence: 99%
“…One‐third of respondents reporting unmet needs blamed problems with the availability of providers. The researchers believe that levels of unmet need in rural Medicaid recipients are “more than double the rate that has been reported by the overall rural population” (Long, Coughlin, and Kendall 2002, p. 443). Hurley, Crawford, and Praeger (2002, p. 165) argue that Medicaid policies carry “the potential for a significant urban bias, depending on the degree of urbanization of a state.” Thus, the Medicaid experiences of rural residents with disabilities are likely to vary across states, with the risk that Medicaid might bolster urban or regional centers at the expense of limiting support of rural providers.…”
Section: Discussionmentioning
confidence: 99%
“…The net effect for this population may have been an increase in access to coverage for care that has limited or no coverage under private policies. It likely also means that more youth and young adults with disabilities must rely on providers that accept Medicaid coverage, which can mean access to fewer providers (Long, Coughlin, and Kendall, 2002 Source: Authors' analysis of the March Supplements for the 1988-1990 Surveys. Estimates are based on data pooled over each three-year period.…”
Section: Resultsmentioning
confidence: 99%